Coronavirus 2019 and health systems affected by protracted conflict: The case of Syria. (July 2020) - Abbara, Aula; Rayes, Diana; Fahham, Ola; Alhiraki, Omar Alrashid; Khalil, Munzer; Alomar, Abdulrahman; Tarakji, Ahmad
Highlights: Conflict-affected settings present particular challenges in the COVID-19 pandemic. Political influences on public health negatively affect COVID-19 control in Syria. Internationally recommended measures may be ineffective or impossible in Syria. Detainees are particularly vulnerable should cases of COVID-19 increase uncontrollably. Rapid capacity building of health systems and staff is needed across Syria to meet needs. Abstract: Introduction: Two thirds of countries globally are unprepared to respond to a health emergency as per the International Health Regulations (2005), with conflict-affected countries like Syria being particularly vulnerable. Political influences on outbreak preparedness, response and reporting may also adversely affect control of SARS-CoV-2 in Syria. Syria reported its first case on 22 March 2020; however, concerns were raised that this was delayed and that underreporting continues. Discussion: Syria's conflict has displaced more than half of its pre-war population, leaving 6.7 million people internally displaced. The consequent overcrowding – with insufficient water, sanitation and healthcare (including laboratory capacity) – could lead to conditions that are ideal for spread of SARS-CoV-2 in Syria. Political changes have led to the formation of at least three health systems within Syria's borders, each with its own governance, capacity and planning. This fragmentation, with little interaction between them, could lead to poor resource allocation and adversely affect control. As such, COVID-19 could overwhelm the health systems (particularly intensive care capacity), leading to high deaths across the population, particularly for the most vulnerable such as detainees. Conclusions: Locally implementable interventions that rapidly build WASH and health system capacity are required across Syria to ensure early detection and management of COVID-19 cases.